Human Rev1 relies on insert-2 to promote selective binding and accurate replication of stabilized G-quadruplex motifs. Issue 4 (8th February 2021) - Ketkar, Amit; Smith, Lane; Johnson, Callie; Richey, Alyssa; Berry, Makayla; Hartman, Jessica H; Maddukuri, Leena; Reed, Megan R; Gunderson, Julie E C; Leung, Justin W C; Eoff, Robert L
Abstract: We previously reported that human Rev1 (hRev1) bound to a parallel-stranded G-quadruplex (G4) from the c-MYC promoter with high affinity. We have extended those results to include other G4 motifs, finding that hRev1 exhibited stronger affinity for parallel-stranded G4 than either anti-parallel or hybrid folds. Amino acids in the αE helix of insert-2 were identified as being important for G4 binding. Mutating E466 and Y470 to alanine selectively perturbed G4 binding affinity. The E466K mutant restored wild-type G4 binding properties. Using a forward mutagenesis assay, we discovered that loss of hRev1 increased G4 mutation frequency >200-fold compared to the control sequence. Base substitutions and deletions occurred around and within the G4 motif. Pyridostatin (PDS) exacerbated this effect, as the mutation frequency increased >700-fold over control and deletions upstream of the G4 site more than doubled. Mutagenic replication of G4 DNA (±PDS) was partially rescued by wild-type and E466K hRev1. The E466A or Y470A mutants failed to suppress the PDS-induced increase in G4 mutation frequency. These findings have implications for the role of insert-2, a motif conserved in vertebrates but not yeast or plants, in Rev1-mediated suppression of mutagenesis during G4 replication.